Teaching during the pandemic: The use of the Google meet platform in Natural Science classes in a school in the County of Parnaíba-PI (Research, Society and Development, 2022)
In recent times, the entire global mass has undergone major adaptations and readjustments due to the pandemic of the new coronavirus, which in addition to impacting everyone's lives, has also brought great technological advances. In the educational context, there was a readjustment to the new teaching-learning methodologies, with remote teaching being the only alternative for the continuation of teaching. Education professionals began to use online tools never before explored, including the Google Meet platform, one of the alternatives for the transmission of online classes. The objective of the present work was to investigate how the Google Meet platform helped in the teaching of Science in the emergency remote modality as an adaptive strategy in the view of students of a public school in the city of Parnaíba, Pi. As an investigation, a questionnaire was developed for data collection, prepared through the Google Forms platform, containing a total of five questions, four of which were subjective and one was objective. The questions applied ranged from evaluations of the meet platform, to the students' opinions about the teaching/learning process with its respective use. Through this work, it was possible to prove the importance of using digital tools such as Google meet, in remote teaching, confirming that they really are alternatives that bring teacher and student closer, filling the gap caused by social isolation.